Attenuated post-exercise heart rate recovery in patients with systemic lupus erythematosus: the role of disease severity and beta-blocker treatment. (February 2018) - Bienias, P; Ciurzyński, M; Chrzanowska, A; Dudzik-Niewiadomska, I; Irzyk, K; Oleszek, K; Kalińska-Bienias, A; Kisiel, B; Tłustochowicz, W; Pruszczyk, P
Objective: Sinus tachycardia is frequently reported in systemic lupus erythematosus (SLE), while there are limited data on post-exercise ability to slow heart rate (i.e. heart rate recovery, HRR) in this group of patients. Methods: We studied consecutive 70 patients with SLE and 30 healthy controls. All examined individuals underwent detailed clinical examination, echocardiography, Holter monitoring with heart rate variability and treadmill stress test using Bruce's protocol. HRR values were calculated as the difference between maximum HR during exercise and HR at the first (HRR1) and third (HRR3) minute of rest. Individuals with coronary artery disease, diabetes mellitus and suspected pulmonary hypertension were excluded from further analysis ( n = 15). Results: Fifty-five SLE patients were eligible for this study: aged 41.5 ± 12.4 years, 87.3% women, SLICC/ACR-DI score 3.58 ± 1.85. In the SLE group 36.4% patients received beta-blockers, usually for previously detected sinus tachycardia and/or arterial hypertension. Mean HRR1 (36.9 ± 12.6 vs 49.5 ± 18.6, p = 0.0004) and HRR3 (55.5 ± 14.3 vs 69.2 ± 16.4, p = 0.0001) were significantly lower in SLE than in healthy individuals. Significantly negative correlations between SLICC/ACR-DI score and HRR1 ( r = –0.299, p = 0.01), HRR3 ( r = –0.361, p = 0.001) and exercise capacity ( r = –0.422, p < 0.0001) were revealed. Additionally, beta-blocker treatment was also revealed to alter significantly HRR1, HRR3 and exercise capacity in SLE. Conclusion: Patients with SLE are characterized by attenuated HRR after exercise. In our study impaired HRR was associated with disease severity and beta-blocker treatment and probably with disease duration. The use of HRR assessment in SLE can be used as an additional marker of cardiac autonomic nervous system dysfunction.